Fintech dan masa depan keuangan: menelusuri peran teknologi dalam mewujudkan keuangan inklusif - Septiana, Yuvi Putri (Maliki Interdisciplinary Journal, 2025)
The development of digital technology has driven significant transformation in the financial sector through the presence of Financial Technology (FinTech). FinTech offers fast, efficient, and easily accessible financial services, so it has great potential in expanding financial inclusion, especially in developing countries and low-income communities. This article aims to explore the strategic role of FinTech in realizing inclusive finance and identify the challenges that accompany it. With a conceptual analysis approach, the discussion covers the contribution of FinTech to the provision of digital financial services such as payments, loans, insurance, and financial education, as well as its impact in reaching groups that were previously underserved by the formal financial system. On the other hand, challenges such as limited digital infrastructure, regulatory gaps, and data security risks are serious obstacles that need to be overcome. The findings of this article emphasize the importance of synergy between the government, regulators, and the FinTech industry to create an inclusive, safe, and sustainable digital ecosystem in order to improve the economic welfare of the community evenly.